GROWING ORAL SPEECH THROUGH THE FORMATION OF CREATIVE THINKING OF PRIMARY SCHOOL STUDENTS - Nafisa Mamarakhimova (Web of Journals Publishing, 2024)
This article discusses how to develop students' creative thinking in their native language and reading literacy classes in primary education through speech development activities.
Keywords: education, upbringing, student, method, speech, speech development, thinking, creative thinking, mother tongue, reading, artwork.